THE PROJECT METHOD FOR THE FORMULATION OF MATHEMATICAL PROBLEMS - Rodríguez Rodríguez, Lázaro E.; García Pimentel, Leticia; Lozano Jiménez , Madeline (Atenas, 2015)
The treatment of the mathematical problems is one of the aspects of the teaching of Mathematics what else contribute the development of the thought. The identification, formulation and problem solving, of these must develop three mathematical capabilities themselves, namely, in his treatment the formulation has been the least taken care of. Learning of the formulation of problems needs the job of methods itself in the process of teaching that they pass over the aulic level, which is why objective of this work constitutes doing an approximation to the utilization of the method of project to contribute to the formulation made suitable of problems by the pupils of the elementary school.